Cage experiments in an East African mangrove forest : a synthesis - Schrijvers, J.; Vincx, M. (J. Sea Res., 1997)
The impact of epibenthos has frequently been investigated for temperate saltmarsh regions by using cage exclusion experiments. Although the insight into the function of the endobenthos of mangove forests is crucial for their management, very few cage experiments have so far been carried out in such areas. The present paper summarises the results of such experiments in a typical Easy African mangrove forest at Gazi Bay about 60 km south of Mombasa, Kenya. Epibenthos animals were excluded for one year in two mangrove zones which differed in forest morphology and intertidal position ( Ceriops tagel and Avicennia marina). Environmental factors and meiobenthic and macrobenthic densities were followed in a randomized block design, and procedural and exclusion effects were statistically detected. In confronting the separate responses of all faunal groups in the two mangrove zone, this synthesis gives a better insight into the tropho-dynamical interactions within this system provided an ideal opportunity to discover the existence of two food systems. This confirmed a strong involvement of the majority of the endobenthos in an isolated decompositional predation in structuring and regulating the global endobenthic community. This synthesis therefore both demonstrates the decisive role of the endobenthos as regenators of mangrove material, and suggets that endobenthos plays a minor role as prey for the demersal or pelagic carnivores.